Thiol-dependent mechanisms of selenium-containing preparations and thiolylfluanide effect on electrolytes leaching and peroxidase activity in Zea mays L. - P. A. Poluboyarinov; N. V. Shchetinina; I. Ya. Moiseeva; N. I. Mikulyak; N. A. Golubkina; A. P. Kaplun (Тонкие химические технологии)
Objectives. While organic and inorganic derivatives of selenium like thiol poisons are known to activate enzymes in cells of different organisms, the mechanism of enzyme activity induction is poorly studied. Therefore, the aim of the study was to investigate the effect of selenium compounds on peroxidase activity induction in maize tissues.Methods. Mechanism of sulfhydryl groups blocking in selenium derivatives was studied on maize in comparison with fungicide tolylfluanid—a typical thiol poison. Electrolytes leakage was determined using conductometry and capillary electrophoresis, protein fractions—by the Ermakov–Durinina method, protein concentration—according to Bradford protein essay, and peroxidase activity—by the Boyarkin method.Results. Diacetophenolylselenide (DAPS-25) was shown to react with SH-groups similarly with tolylfluanid fungicide. DAPS-25 increased K+ and leakage by 58 and 14 times, while appropriate increases for tolylfluanid were 4.4 and 1.5 times as compared to control. Increased total protein content—especially albumins—was due to electrolyte leakage from maize cells. DAPS-25 increased albumins concentration by 2.4–4.5 times, and tolylfluanid application by 2 times. Similar increase of peroxidase activity in maize roots and sprouts as a result of DAPS-25 (by 63% and 112%) and tolylfluanid (by 73% and 63%) application indicates close mechanism of their effect. Under DAPS-25 loading L-cysteine decreases peroxidase activity, which records the removal of SH-groups blockage. A less intensive effect was registered for sodium selenite and L-selenocystin, also capable of reacting with SH-groups. L-cysteine supplementation to DAPS-25 solution decreases selenium concentration in maize, indicating the decrease of selenium bioavailability.Conclusions. The results indicated that selenium containing compounds react with SH-groups of maize cells increasing electrolytes leakage, protein content and especially albumins resulting in the increase of peroxidase activity.